Development of extraction method for characterization of free and bonded polyphenols in barley (Hordeum vulgare L.) grown in Czech Republic using liquid chromatography-tandem mass spectrometry - Arigó, Adriana; Česla, Petr; Šilarová, Petra; Calabro, Maria Luisa; Česlová, Lenka (Elsevier Science, 2018)
Complete characterizations of free and bonded phenolic compounds, presented in four cultivars of barley from two regions of Czech Republic, were achieved, using optimized solvent extraction and liquid chromatography coupled with tandem mass spectrometry. The optimization of extraction of free polyphenols was performed using Box-Behnken design and response surface methodology. The intra-day and extra-day precision of developed method were below 6% and 12%, respectively. The isolation of polyphenols bonded to the cell wall structure was carried out by a hydrolysis process. In all cultivars, p-hydroxybenzoic, p-coumaric and ferulic acids were the most abundant compounds. Their average amounts in barley samples were 17.6, 15.2 and 54.4% (m/m), respectively. The highest amount of these compounds was found in the bonded form, proving the importance of this procedure for the correct characterization of total polyphenols in food matrices.
Vývoj extrakční metody pro charakterizaci volných a vázaných fenolických látek v ječmeni pomocí LC-MS
Keywords: Barley; Free and bonded polyphenols; Hydrolysis; RP-HPLC-MS/MS; design-of-experiment; volné a vázané fenolické látky; hydrolýza; RP-HPLC-MS/MS; DOE